Game and Ritual Practices in the Russian Literature of the 19th Century - Коковина, Наталья (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The article discusses a range of phenomena for which 19th-century literature established the name of game. In the study of symbolic behaviour, one of the most confusing questions is that of the relationship between game and ritual. Fluid boundaries between them and lack of clear idea of the nature of these phenomena have often lead to a widening of the scope of the concepts: game has been thought to include ritual behaviours, and the other way round.